2014
DOI: 10.1186/1743-8977-11-8
|View full text |Cite
|
Sign up to set email alerts
|

Sub-chronic toxicity study in rats orally exposed to nanostructured silica

Abstract: BackgroundSynthetic Amorphous Silica (SAS) is commonly used in food and drugs. Recently, a consumer intake of silica from food was estimated at 9.4 mg/kg bw/day, of which 1.8 mg/kg bw/day was estimated to be in the nano-size range. Food products containing SAS have been shown to contain silica in the nanometer size range (i.e. 5 – 200 nm) up to 43% of the total silica content. Concerns have been raised about the possible adverse effects of chronic exposure to nanostructured silica.MethodsRats were orally expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
156
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(168 citation statements)
references
References 42 publications
10
156
0
2
Order By: Relevance
“…When focusing on the liver, the calculated liver concentrations at the effect level differ by a factor seven between the NCI study and the study of Wang et al (2013). This difference in internal concentration may well be explained by animal variation, a lower absorption at the very high doses up to 2500 mg/kg bw/d in the NCI study, as seen for silica (van der Zande et al, 2014), or a smaller fraction of NPs in the tested titanium white in the NCI study. Peters et al (2014) found a range of 0.012-0.31% NPs (by weight) in seven different brands of E 171 and for the NCI study the highest measured fraction of 0.31% was assumed as a worst-case scenario.…”
Section: Reflection On Risk Assessment Outcomementioning
confidence: 87%
See 1 more Smart Citation
“…When focusing on the liver, the calculated liver concentrations at the effect level differ by a factor seven between the NCI study and the study of Wang et al (2013). This difference in internal concentration may well be explained by animal variation, a lower absorption at the very high doses up to 2500 mg/kg bw/d in the NCI study, as seen for silica (van der Zande et al, 2014), or a smaller fraction of NPs in the tested titanium white in the NCI study. Peters et al (2014) found a range of 0.012-0.31% NPs (by weight) in seven different brands of E 171 and for the NCI study the highest measured fraction of 0.31% was assumed as a worst-case scenario.…”
Section: Reflection On Risk Assessment Outcomementioning
confidence: 87%
“…It is unknown whether the doses used in the toxicity studies, which are all much higher than human intakes (4250-fold) and are given as a daily bolus dose in most studies instead of consumption and thus gradual uptake during the day, are absorbed differently than the amounts ingested by humans. SiO 2 NPs have been reported to gelate at higher doses in the gut (van der Zande et al, 2014), resulting in lower oral absorption at a high dose than at lower doses. We are not aware of studies indicating whether TiO 2 NPs can gelate as well in the gut, although it is common knowledge that NP aggregation increases with concentration.…”
Section: Uncertainties and Assumptionsmentioning
confidence: 99%
“…Известны многочисленные исследования, доказываю-щие цитотоксическое действие наночастиц оксида кремния при их ингаляции на произ-водстве [4,5]. Помимо дыхательных путей, наночастицы могут попадать в организм и через желудочно-кишечный тракт [6,7].…”
Section: экспериментальная медицинаunclassified
“…This means that we are only interested in the median particle size. Considering various studies, we assumed a median particle size of 100 nm (Peters et al, 2012;van der Zande et al, 2014 Hazard is expressed as the Individual Benchmark Dose (IBMD), which is the dose at which an individual human experiences a predefined response to a substance (higher IBMD means lower hazard). Starting from a B M D ani mal obtained from a dose-response modelling of data from an animal study, the IBMD is calculated using the formula…”
Section: Methodsmentioning
confidence: 99%
“…This choice was based on studies (Peters et al, 2012;van der Zande et al, 2014) in which particle sizes were measured. Due to the limitations of the instrumentation and the difficulty in measuring single particles in a large agglomeration such as found in food products, a perfect estimate for the median particle size was not possible.…”
Section: Limitationsmentioning
confidence: 99%